Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


The equation to be proved is n(n+1)(n+2)=6 times something.
For n=1,
LHS= 6
RHS= 6= LHS.
Let n=k hold true for any other +ve value.
Therefore, k(k+1)(k+2)=6m
Now to prove that n=k+1 is also true,
Substitute k+1 in place of n or k to get (k+1)(k+2)(k+3)
=6 times something
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts